Teacher’s Strategies in Teaching English Vocabulary at Elementary School: A Case Study at First Grade Students of Elementary School 3 Karang Bongkot West Lombok, Academic Year 2024/2025 - Rahman, Latifa Nurul Anggraeni Sophia; Arafiq,; Susanti, Ni Wayan Mira; Elmiana, Dewi Satria (Journal of Authentic Research, 2025)
This study investigates the strategies employed by English teachers in teaching vocabulary to first-grade students at Elementary School 3 Karang Bongkot, West Lombok, during the academic year 2024/2025. The study aims to identify the challenges faced by teachers and describe the effective strategies used to overcome these challenges. The method of this research was qualitative research. The subject is an English teacher of SDN 3 Karang Bongkotwho taught the first grade. Data were collected through classroom observations and semi-structured interviews. The findings reveal several challenges, including classroom management, diversity of students’ mother tongue, and limited teaching facilities or media. To overcome these barriers, the teacher applied the Total Physical Response (TPR) through songs and games supported with translation, memorization, and visual aids like printed pictures. These approaches successfully increased student participation, maintained focus, and created a more enjoyable learning atmosphere. The study concludes that effective vocabulary learning for young learners depends on the teacher’s creativity in combining methods, techniques, and media suited to children’s characteristics.